Analisis Putusan MA Perkara No 916/Pdt.P/2022/PN.Sby Dalam Mengabulkan Permohonan Pencatatan Nikah Beda Agama Dalam Perspektif Undang-Undang Perkawinan No 1 Tahun 1974 - Hakim, Anwar; Soderi, Ridhokimura (Institut Agama Islam Negeri (IAIN) Curup, 2022)
Abstract: Interfaith Marriage in the Perspective of Marriage Law No. 1 of 1974 (Review of Analysis of Article 2 of Law No. 1 of 1974 concerning Marriage). Indonesia is a country with a multi-religious society. The various religions and beliefs held by the Indonesian people open up the potential for interfaith marriages. Interfaith marriages often cause polemics in society, this is because in Indonesia interfaith marriage is something that is considered uncommon and contrary to religious beliefs held by the majority of Indonesian people. In Indonesia, the rules related to marriage are contained in Law No. 1 of 1974 concerning Marriage and the Compilation of Islamic Law. Article 2 of the Marriage Law No. 1 of 1974 states that